INDONESIA'S REJECTION OF ISRAEL IN THE 2023 U-20 WORLD CUP: AN INTERNATIONAL LAW PERSPECTIVE - Putra M, Hilton Tarnama; Fachriza, Afda; Susanti, Hera; RE, Pengleang (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Sport is a significant aspect of international relations. In 2023, FIFA planned to hold the U-20 World Cup in Indonesia, but the event was canceled after Indonesia rejected Israel's participation. This research aims to analyze whether a country has the authority to exclude other nations from sports events under international law, and whether Indonesia's actions in rejecting Israel's participation align with international legal principles. The study uses a normative legal research method, focusing on relevant legal norms and frameworks. The findings indicate that, according to international law, a state’s sovereignty allows it to make decisions regarding participation in international events, as outlined in the general principles of law and the 1933 Montevideo Convention. These principles affirm a nation's right to control its territory, including its policies on human rights, in line with the Universal Declaration of Human Rights and FIFA's Statutes. Furthermore, the legal basis for Indonesia's rejection of Israel is supported by national laws, including the 1945 Constitution’s preamble and the Ministry of Foreign Affairs Regulation No. 3 of 2019, which sets guidelines for Indonesia’s foreign relations, particularly with Israel. The contribution of science in this research is an analysis of the legality of state actions in the context of rejecting the participation of other countries in international sports events, by considering the principle of state sovereignty and international legal obligations